Health promotion to people with disabilities: case report from two University extension projects (Research, Society and Development, 2022)
Developing Health Promotion programs and interventions for people with disabilities during undergraduate health courses represents a relevant strategy to ensure comprehensive, equitable and universal care. Objective: to describe and reflect on two Brazilian experiences focused on promoting the health of people with physical disabilities within the scope of university extension. Method: this is the report of experiences derived from the “Praia Sem Barreiras” Project in Recife (PE) and the “Remo Meu Rumo” Project in São Paulo (SP), Brazil. Results: both activities are interdisciplinary, interprofessional and intersectoral. They focus on relationships between Higher Education Institutions and articulate community partnerships focusing on well-being, self-care and physical activity and leisure. Final Considerations: it is evident that the performance of undergraduate health students and professors excelled in the use of public spaces in the city as a powerful strategy for social inclusion, collaborative learning and the exercise of citizenship. However, it is necessary to broaden the discussion on developing Health Promotion skills to prepare the health sector workforce with greater sensitivity to the needs of people with disabilities or reduced mobility.